Animation and the programmed abstract aesthetic :an exploration into the impossibly real through the medium of particle system simulation - Shachman, Michal (My University, 2013)
Short Description The impossibly real and its manifestations in Digital Abstract Animation are explored in order to experiment with the abstract, programmed aesthetics inherent in the computational logic of Particle System Simulation. Long Description The production of animated film content throughout the 20th and the 21st century has not only seen the progression of representational film and digital video works but also extensive explorations into the abstract. A trend that is evident is that what is real and what is not real in digital representation has since become increasingly intertwined into the abstract and so it is proposed that a further representation of the real needs to be considered and investigated. In this research project it is proposed that the idea of the impossibly real is this further representation of the real and is inherent in the role of abstraction and the computational logic of a digital system which calculates reality to constitute a simulated visual production. The author supports this with an investigation of the tradition of 20th century nonrepresentational animation up until and including the advancement into a digital medium in 21st century digital art and practice. As an entry point the author reappropriates the technology of the programming method of Particle System Simulation in the Softimage 2012 ICE (Interactive Creative Environment) Simulation Engine to explore the computational logic of data-parameter manipulation as a programmed abstract aesthetic with great potential artistic value. As part of the Creative Component of this research project is an exhibited series of experimental digital Abstract Animation video 3 artwork, produced to practically explore manifestations of the impossibly real. The impossibly real is not real, but in this research project it proposed as a further representation of the real that could surpass the need for realist representation and interpretation in digital productions in the future.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, School of Digital Arts (Digital Animation), 2012